Towards the Promotion of Positive Development among Youth in Challenging Contexts: A Mixed-Methods Study of Engagement in the ScoutReach Program - Champine, Robey. (2017)
Abstract: The experiences of male youth of color in urban and lower-income communities (e.g., related to exposure to racism, antisocial behaviors, and conflicting cultural norms in regard to masculine identity and behavior) may constrain their capacity to develop positive self-judgments and hopeful future-oriented beliefs. However, these youth may have access to external resources that buffer them against potential contextual risk factors. Youth development (YD) programs (e.g., Boy Scouts of America [BSA]) may represent key ecological developmental assets in the individual-context developmental systems of these youth that are linked to thriving and reduced likelihood of problematic developmental trajectories. Engagement is an important dimension of participation in YD programs that reflects the quality of young people's involvement, their degree of investment, and how they make meaning of their experiences. However, more research is needed that explores cognitive, emotional, and behavioral dimensions of engagement in YD programs that serve underrepresented male youth. Accordingly, this cross-sectional and mixed-methods study, informed by relational developmental systems metatheory and the Phenomenological Variant of Ecological Systems Theory, sought to enrich understanding of the experiences of male youth of color in ScoutReach, an arm of BSA that aims to make Scouting more accessible to culturally diverse youth from lower-resource communities. I analyzed questionnaire data from 32 Scouts enrolled in two ScoutReach units in the greater Boston area, interview data from 10 Scouts,10 parents/guardians, and five program leaders, and short-answer questionnaire responses from 32 parents/guardians. These analyses primarily explored different dimensions of youth engagement in the program and relations among these dimensions and indicators of positive and potentially problematic youth development. Quantitative results suggested that Scouts demonstrated different dimensions of engagement in ScoutReach, and that these dimensions were related differentially to indicators of positive and potentially problematic youth development. Qualitative results revealed similarities and differences in stakeholder groups' views of ScoutReach and how the program may be impacting youth development. These data also elucidated aspects of the program context that were linked to youth engagement. For instance, whereas Scouts and program leaders primarily described camping and other outdoor activities as strongly linked to youth engagement and positive development, parents/guardians more strongly emphasized Scouts' interpersonal relationships in the program. When analyzed together, these quantitative and qualitative findings indicated nuanced relations among dimensions of engagement and indicators of youth development and, as well, nuances in individuals' perceptions of (and experiences in) ScoutReach and Scouts' communities. I discuss limitations of the study and potential implications for future research and practice.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Child Development.; Advisor: Richard Lerner.; Committee: Ellen Pinderhughes, Sara Johnson, and Michael Cunningham.; Keyword: Developmental psychology.